Prevalence and Associated Factors of Violence against Hospital Staff at Amanuel Mental Specialized Hospital in Addis Ababa, Ethiopia. (5th November 2019) - Abate, Ayalew; Abebaw, Dessie; Birhanu, Addis; Zerihun, Aemero; Assefa, Dawit
Abstract : Background. Violence at the workplace has become an alarming phenomenon worldwide. The real size of the problem is largely unknown and recent information shows that the current knowledge is only the tip of the iceberg. The enormous cost of violence at the workplace for person and community at large is becoming more apparent. It could be physical, sexual, and verbal in nature and could be actual or threatened. Objectives. To access prevalence and associated factors of violence against hospital staff at Amanuel Mental Specialized Hospital Addis Ababa, Ethiopia. Methods. An institution based cross-sectional study was employed in 2017. The data were collected using Workplace Violence in the Health Sector Country Case Study Questionnaire from 496 participants. Participants had been selected using simple random sampling technique and data were collected using a self-administered structured questionnaire. The collected data were entered into Epi-data version 3.1, and SPSS version 21 was used for Analysis. Binary logistic regression was fitted to identify factors associated with the outcome variable. Result. From 496 staff intended to have participated in this study, complete data were obtained from 435, making a response rate of 87.7%. This research showed high prevalence of violence and we have got that staff had been exposed to physical violence 36.8%, verbal violence 62.1%, and sexual violence 21.8 % over the past year, respectively. Age, sex, and contact with the patient were statistically significant variables (p < 0.05 ). Conclusion and Recommendation. According to this study, majority of AMSH staff were violated by the patient they care.